2016
DOI: 10.1039/c6nr02228f
|View full text |Cite
|
Sign up to set email alerts
|

A smart multifunctional drug delivery nanoplatform for targeting cancer cells

Abstract: Wirelessly guided magnetic nanomachines are promising vectors for targeted drug delivery, which have the potential to minimize the interaction between anticancer agents and healthy tissues. In this work, we propose a smart multifunctional drug delivery nanomachine for targeted drug delivery that incorporates a stimuli-responsive building block. The nanomachine consists of a magnetic nickel (Ni) nanotube that contains a pH-responsive chitosan hydrogel in its inner cavity. The chitosan inside the nanotube serves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…Such a property is particularly useful for regulating the loading region and controlling the release sequence for different drugs, which is crucial for realizing cascade release of multiple drugs. The controlled release of different therapeutic agents from hybrid hydrogels can be regulated either by internal stimuli offered by polymers (e.g., pH, 2 Once GO is incorporated into thermo-sensitive hydrogels, it will convert NIR light into heat and further trigger an expansion/contraction or gel-sol transition of the hydrogels to release cargos. However, to the best of our knowledge, few works have touched on the cascade release of multiple drugs from GO-based hydrogels with NIR light control.…”
mentioning
confidence: 99%
“…Such a property is particularly useful for regulating the loading region and controlling the release sequence for different drugs, which is crucial for realizing cascade release of multiple drugs. The controlled release of different therapeutic agents from hybrid hydrogels can be regulated either by internal stimuli offered by polymers (e.g., pH, 2 Once GO is incorporated into thermo-sensitive hydrogels, it will convert NIR light into heat and further trigger an expansion/contraction or gel-sol transition of the hydrogels to release cargos. However, to the best of our knowledge, few works have touched on the cascade release of multiple drugs from GO-based hydrogels with NIR light control.…”
mentioning
confidence: 99%
“…Clearly, this biomolecular fluorophore labeling strategy not only enabled the visualization of the movement of the hybrid particles in in vitro experiments but also confirmed that these structures resemble the motion of self‐propelling flagellated bacteria found in nature (Figure c). Recently, Hoop et al developed a smart multifunctional drug delivery nanoplatform for targeting cancer cells that was biolabeled . In this work, the nanomachine consisted of a magnetic tube with a pH‐responsive chitosan hydrogel in its inner cavity.…”
Section: Imaging Technologies For Micro‐ and Nanoswimmersmentioning
confidence: 99%
“…e,f) Optical and fluorescence microscopy images of functionalized nanotubes with a FITC‐tagged ssDNA. (e,f) Reproduced with permission . Copyright 2016, Royal Chemical Society.…”
Section: Imaging Technologies For Micro‐ and Nanoswimmersmentioning
confidence: 99%
“…When the rotating plane of the nanowire is perpendicular to the surface, the interaction of the nanowire with the surface will cause a velocity difference between the two ends of the nanowire, which changes the center of rotation and results in the propulsion of the nanowire. This idea was demonstrated by Zhang et al using Ni nanowires (Figure 6a)[10], and adapted later to some other magnetic nanowire systems[3,6,71]. Taking advantage of the vortex generated by the rotating motion, surface walkers can transport and manipulate small cargos[10].…”
mentioning
confidence: 93%
“…Micro-and nanorobots are promising devices for applications in drug delivery, sensing, environmental remediation, and manipulation of small objects [1][2][3][4][5][6][7][8][9][10][11]. These machines convert energy into motion by scavenging fuel from their surrounding media [12][13][14][15][16][17][18], or by harnessing power from external energy sources such as light, ultrasound, electrical or magnetic fields, or combinations of these [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%